2013
DOI: 10.2174/1573406411309060006
|View full text |Cite
|
Sign up to set email alerts
|

Screening of SdiA Inhibitors from Melia dubia Seeds Extracts Towards the Hold Back of Uropathogenic E.coli Quorum Sensing-Regulated Factors

Abstract: Plants have always been a supreme source of drugs and India is endowed with a wide variety of them with high medicinal values. The Quorum Sensing (QS) quenching efficiency of various solvent extracts of Melia dubia seeds was investigated against uropathogenic Escherichia coli (UPEC) to screen the competitive inhibitor of SdiA, a transcriptional activator of quorum sensing in E. coli. In this study, potentiality of five different extracts of Melia dubia seeds for quorum sensing inhibitory activity was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The present study involves the screening, synthesis and validation of a potent compound against SarA of S. aureus associated with gestational urinary tract infections, in light of our previous studies that showed potent antibiofilm activity in root ethanolic extract of M. dubia against uropathogenic E. coli (Vinothkannan et al, 2013 ; Adline Princy et al, 2014 ) and antibiofilm activity of SarABI against S. aureus associated with vascular graft infections (Arya et al, 2015 ). In brief, the proposed inhibitor, UTI QQ against SarA protein was computationally validated to have a high affinity toward the target and it was synthesized by a two step process, i.e., reductive amination and steglich esterification for further in vitro and in vivo validation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study involves the screening, synthesis and validation of a potent compound against SarA of S. aureus associated with gestational urinary tract infections, in light of our previous studies that showed potent antibiofilm activity in root ethanolic extract of M. dubia against uropathogenic E. coli (Vinothkannan et al, 2013 ; Adline Princy et al, 2014 ) and antibiofilm activity of SarABI against S. aureus associated with vascular graft infections (Arya et al, 2015 ). In brief, the proposed inhibitor, UTI QQ against SarA protein was computationally validated to have a high affinity toward the target and it was synthesized by a two step process, i.e., reductive amination and steglich esterification for further in vitro and in vivo validation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, five inducers and three inhibitors which are molecularly distant from the native autoinducer N-3-oxododecanoyl-Lhomoserine lactone have been investigated as potential QQ compounds (26). As another example of these modeling approaches, competitive inhibitors of SdiA, a signal receptor of the QS signals of other bacteria in Escherichia coli, have been screened from Melia dubia seed extracts, and 27 compounds structurally unrelated to autoinducers show potential for attenuating QS in uropathogenic E. coli (27). Also, molecular docking was used to identify potential QQ compounds from bark extracts of the mangrove plant Rhizophora annamalayana (28).…”
mentioning
confidence: 99%
“…The review has highlighted the importance of QS pathway in S.mutans and its role in formation of biofilm along with other virulence properties. Quite a few efforts has been taken to modulate QS to reduce the production of biofilm and associated virulence factors like Hentzer and Givskov, Ravichandran et al, Arya et al, Hema et al, and Wright et al, have described the application of antagonists that act as QS inhibitors to attain the inhibition of virulence genes under QS circuit to prevent the various infections caused by Pseudomonas aeruginosa, Vibrio cholerae and Staphylococcus aureus [28,33,[70][71][72][73][74][75][76]. The approach ensures its success in the fact that, anti-quorum compounds may control virulence traits of pathogenic microbes without significant effects on viability of bacterial cells [77].…”
Section: Resultsmentioning
confidence: 99%